2020
DOI: 10.3390/nu12103076
|View full text |Cite
|
Sign up to set email alerts
|

What Do Polish Parents and Caregivers Think of Dietary Supplements for Children Aged 3–12?

Abstract: Background: The aim of this study was to specify the amounts and the types of dietary supplements (DS) taken by children and define the attitudes of caregivers towards DS and towards administering them to children aged 3–12. An analysis of the reasons for using DSs, and of expected benefits and awareness of health risks associated with administering DSs, was conducted. Methods: The online questionnaire collected information on sociodemographic characteristics and use of dietary supplements. Multiple analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 56 publications
(63 reference statements)
2
18
0
2
Order By: Relevance
“…In this and other works [19,[21][22][23], researchers also use personally designed questionnaires to interview the population. And the result of the data received by them is confirmation of the opinion on the need for additional information and explaining to the public the responsibility for self-medication, its possible negative consequences, as well as aspects of the correct choice of drugs [11,13,20,24].…”
Section: Discussion Of Research Resultsmentioning
confidence: 84%
“…In this and other works [19,[21][22][23], researchers also use personally designed questionnaires to interview the population. And the result of the data received by them is confirmation of the opinion on the need for additional information and explaining to the public the responsibility for self-medication, its possible negative consequences, as well as aspects of the correct choice of drugs [11,13,20,24].…”
Section: Discussion Of Research Resultsmentioning
confidence: 84%
“…Parents who gave dietary supplements to their children tended to be more trusting of such products than those who did not. It was confirmed that parents transfer their own behavioural patterns to their children, so those who themselves used dietary supplements also gave them to their children [14].…”
Section: Discussionmentioning
confidence: 89%
“…The main reasons were: improving immunity against flu and infections, protecting against adverse effects of antibiotics, and increasing the intake of vitamins and minerals. 10 …”
Section: Food Supplements: Perception Of Usementioning
confidence: 99%